Membership Verification in Authenticating Dynamic Sets - Wei, Zukuan; Kim, Hongyeon; Kim, Youngkyun; Kim, Jaehong (International Journal of Online and Biomedical Engineering (iJOE), 2013)
A file system for cloud storage has to guarantee integrity of its files. For this purpose, existing designs mainly rely on hash tree and RSA tree. A new design based on B+ tree construction is proposed in this paper. The new design performs better in dynamic authentication for integrity of file system and also relatively has low computational cost.